Respuestas

  • Usuario de Brainly
2014-01-15T04:03:09+01:00
Cotan(a)sec( =cosec(a)
cos(a)/sen(a) * 1/cos(a) =cosec(a)
1/sen(a) =cosc(a)
cosc(a) =cosc(a)

tanx+cotx = secxcoscx    uso x por comodidad
senx/cosx + cosx/senx = secxcoscx
[sen^2(x) + cos^2 (x)]/cosx senx = secxcoscx
1/cosxsenx = secxcoscx
1/cosx*1/senx = secxcoscx
secxcoscx = secxcoscx

1+cot^2(x) =csc^2(x)
1+ cos^2(x)/sen^2(x) =csc^2(x)
[(sen^2(x)+cos^2(x)]/sen^2(x) = csc^2(x)
1/sen^2(x) = csc^2(x)
csc^2(x) =csc^2(x)













Muchas gracias por la ayuda BENDICIONES!!